2014
DOI: 10.1097/jto.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Development of Renal Cysts after Crizotinib Treatment in Advanced ALK-Positive Non–Small-Cell Lung Cancer

Abstract: Change of renal cysts after crizotinib treatment is not uncommon. Development of complex renal cysts reverses after stopping crizotinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 13 publications
(8 reference statements)
0
73
1
1
Order By: Relevance
“…A series from Taiwan found changes in renal cysts in seven (22 %) of 32 patients who received crizotinib for ALK-positive advanced NSCLC [83]. In a recent analysis of 255 patients treated with crizotinib for at least 6 months, 9 % had developed new cysts, and 2 % had both new cysts and size increases in existing cysts of more than 50 % [84].…”
Section: Renal Cystsmentioning
confidence: 96%
“…A series from Taiwan found changes in renal cysts in seven (22 %) of 32 patients who received crizotinib for ALK-positive advanced NSCLC [83]. In a recent analysis of 255 patients treated with crizotinib for at least 6 months, 9 % had developed new cysts, and 2 % had both new cysts and size increases in existing cysts of more than 50 % [84].…”
Section: Renal Cystsmentioning
confidence: 96%
“…Lin et al [14] evaluated 32 patients in 3 clinical trial and also found significant reduction in the size of renal cysts after treatment suspension. The patients who had significant renal cyst changes received Crizotinib for longer duration (median, 956 days versus 248 days, p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib increases the risk of renal cysts development and also increases pre-existing cystic lesions [12] [14].…”
Section: Discussionmentioning
confidence: 99%
“…Po vysazení crizotinibu došlo k normalizaci eGFR k hodnotám před zahájením léčby. Etiologie této toxicity může úzce souviset s vyšší pravděpo-dobností vzniku nových a ve zvětšení již přítomných cyst ledvin [29,30].…”
Section: Inhibitory Alkunclassified